Motives issues some primary school students have in learning some foreign languages - Čiurlienė, M. (Psichologija, 1968)
This article deals with the peculiarities of foreign language learning motives of some primary school children. The survey results show that almost all primary school students who learn foreign languages have quite clearly expressed motives. The school environment helps to form learning motives and can give behavior purposefulness. Nearly two-thirds of primary school students have a negative opinion about foreign language learning.